2014
DOI: 10.1002/art.38322
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate and Lung Disease in Rheumatoid Arthritis: A Meta‐Analysis of Randomized Controlled Trials

Abstract: Objective. Methotrexate has shown efficacy for the treatment of several diseases, especially rheumatoid arthritis (RA). Methotrexate has also been implicated as a causative agent in interstitial lung disease. Patients with RA may develop pulmonary manifestations of their disease and are at increased risk of respiratory infection. The aim of this study was to evaluate the relative risk (RR) of pulmonary disease among patients with RA treated with methotrexate.Methods. We searched the PubMed and Cochrane databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
121
0
16

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(156 citation statements)
references
References 59 publications
(77 reference statements)
9
121
0
16
Order By: Relevance
“…There have been reports of lymphoproliferative diseases developing in the setting of methotrexate treatment, with disease regression once medication is stopped. A recent meta-analysis of 22 studies involving rheumatoid arthritis patients treated with methotrexate (n=4544) versus other agents (including disease modifying anti-rheumatic drugs and biological agents) found a small increase in risk of respiratory infections (RR 1.11, 95% CI 1.02-1.21), but not in noninfectious complications, such as pneumonitis, or death from pulmonary causes among those treated with methotrexate [95].…”
Section: Methotrexatementioning
confidence: 99%
“…There have been reports of lymphoproliferative diseases developing in the setting of methotrexate treatment, with disease regression once medication is stopped. A recent meta-analysis of 22 studies involving rheumatoid arthritis patients treated with methotrexate (n=4544) versus other agents (including disease modifying anti-rheumatic drugs and biological agents) found a small increase in risk of respiratory infections (RR 1.11, 95% CI 1.02-1.21), but not in noninfectious complications, such as pneumonitis, or death from pulmonary causes among those treated with methotrexate [95].…”
Section: Methotrexatementioning
confidence: 99%
“…Most generally used disease-modifying antirheumatic drugs (DMARDs), methotrexate (MTX), is suspicious for causal agent of lung disease. According to recent meta-analysis of randomized controlled trials, MTX increased the risk of lung disease significantly compared to other DMARDs and biologic agents [12]. But the amount of risk increase was very small (10%) and the scope of lung diseases in this meta-analysis included all adverse respiratory events including infection.…”
Section: Lung Disease In Rheumatoid Arthritismentioning
confidence: 90%
“…Studies have shown that pneumonitis may complicate low-dose MTX therapy as well (3). A recent meta-analysis showed that the risk of pneumonitis is significantly increased in RA patients treated with MTX (relative risk 7.8), but did not show an increased risk of death due to lung disease in this population (4). Common findings on chest radiographs in MTX pneumonitis include interstitial or mixed interstitialalveolar infiltrates; HRCT usually demonstrates multifocal ground-glass opacities.…”
Section: Differential Diagnosismentioning
confidence: 97%